STUDI KORELASI ANTARA LINGKUNGAN SOSIAL DENGAN AKTIVITAS BELAJAR SISWA KELAS VIII SMP NEGERI I SINGOJURUH KABUPATEN BANYUWANGI SEMESTER II TAHUN PELAJARAN 2016/2017 - Heriberthus Wicaksono; Agus Mursidi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2017)
The social environment is divided into family, class, and outside class environments. The most important thing is the family environment, as formal and informal education. The existence of a social environment indirectly contributes to student learning activities. In taking research data using quantitative methods to obtain accurate results using the chi square method so that the results show there is a correlation of 0.924 or 92.4% classified as very high correlation. In this case the correlation size cannot reach the maximum correlation (100%), so there is still 7.6% which is not correlated. This is because there are still some low questionnaire values